2014
DOI: 10.1007/s00246-014-0937-z
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Rate-Corrected QT Interval Evolution in Premature Infants During the First Week of Life

Abstract: Automated monitoring of the QT interval is increasingly common in a variety of clinical settings. A better understanding of how the heart-rate-corrected QT interval (QTc) evolves in early postnatal life is needed before its clinical utility in neonates can be determined. This study aimed to use real-time bedside monitoring as a tool to describe the QTc evolution of premature neonates during the first week of life. All neonates born at a gestation age (GA) of 31 weeks or later and admitted to the level 2 intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A study enrolling newborn preterm infants found that HRV is progressively present in the first 3 to 4 days of life and forms a stable base after this period; the study further demonstrated that there is a reduction in ANS modulation at the onset of preterm infant life [18]. With the inadequate functioning of the SNA, the organism tends towards linearity, with the expected changes and adaptations not occurring.…”
Section: Discussionmentioning
confidence: 99%
“…A study enrolling newborn preterm infants found that HRV is progressively present in the first 3 to 4 days of life and forms a stable base after this period; the study further demonstrated that there is a reduction in ANS modulation at the onset of preterm infant life [18]. With the inadequate functioning of the SNA, the organism tends towards linearity, with the expected changes and adaptations not occurring.…”
Section: Discussionmentioning
confidence: 99%
“…We previously studied the same QTc "data sniffer" and patient population and found that neonatal QTc is highly variable during the first 3 to 4 days of life and undergoes a gradual decline toward lower and more stable values among all age groups. 16 Using standard means and SDs from that study, we determined a cutoff (>475 ms after day of life three) that would capture those infants most at a risk of QTc prolongation on 12-lead ECG and selected those infants for more "traditional" ECG screening.…”
Section: Discussionmentioning
confidence: 99%
“…A threshold of 475 ms was chosen as this represented >2 standard deviation (SD) during a previous population-based pilot study performed in the same unit. 16 When QTc prolongation was detected, the DS triggered an automated page and e-mail to the on-call neonatologist covering the level II NICU.…”
Section: Data Sniffermentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Prolonged QT c interval can be normal in the first few days of life in premature neonates, hence it is difficult to identify drug-induced aetiology during this period. 44 …”
Section: Discussionmentioning
confidence: 99%